DAMPAK FATWA DSN MUI TERHADAP LAPORAN KEUANGAN SYARIAH DI INDONESIA - Irzan; Fiona Gea Az-Zahra; Alda Lorenza (Yayasan Nuraini Ibrahim Mandiri, 2025)
The DSN-MUI Fatwa acts as the main guideline in ensuring that Islamic financial products and services are in accordance with Islamic sharia principles, as well as being an important instrument in encouraging product innovation and increasing public confidence in Islamic finance. So this study aims to determine how much impact the DSN-MUI Fatwa has on the Sharia Financial System in Indonesia. The technique used in this research uses the Systematic Literature Review (SLR) method. In this study, the articles obtained were 30 articles indexed by Sinta. The results of the analysis show that the impact of the DSN-MUI Fatwa on the Sharia Financial System in Indonesia.